Pomen magnetnoresonančnih metod pri raziskavah ogrodnih tablet s podaljšanim sproščanjem - Mikac, Urška (Farmacevtski vestnik, 2016)
The drug release form polymer matrix tablets is a complex process, greatly influenced by the gel's formation at the tablet surface. Magnetic reso- nance (MR) is a non-invasive method suitable to determine the gel layer properties by using MR that can provide the information about the gel's properties. MR imaging (MRI) that enables in situ determination of tablet swelling and can provide the polymer concentration profile during swelling; Combination of MRI and USP-4 aparatus enables in situ determination of tablet swelling and drug release kinetics or by using special MRI techniques enabling the determination of distribution of the polymer and the drug in the tablet at the same time. The combination of the data obtained by MR techniques, mathematical model, and other analytical methods makes the polymer matrix ta- blets design more successful.
Keywords: gel; ksantan; magnetna resonanca; nabrekanje; ogrodne tablete; tablete